2010
DOI: 10.1186/1471-2229-10-95
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the CRK/DUF26 group of Receptor-like protein kinases by ozone and plant hormones in Arabidopsis

Abstract: BackgroundPlant Receptor-like/Pelle kinases (RLK) are a group of conserved signalling components that regulate developmental programs and responses to biotic and abiotic stresses. One of the largest RLK groups is formed by the Domain of Unknown Function 26 (DUF26) RLKs, also called Cysteine-rich Receptor-like Kinases (CRKs), which have been suggested to play important roles in the regulation of pathogen defence and programmed cell death. Despite the vast number of RLKs present in plants, however, only a few of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
253
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(266 citation statements)
references
References 83 publications
11
253
0
2
Order By: Relevance
“…Several mutants altered in hormone biosynthesis or signalling showed also changes in ozone-induced transcriptional responses. 134 Gauthier et al 135 have identified two members of the cysteine-rich receptor-like kinase gene family and a leucine-rich repeat (LRR-RLK) protein in Arabidopsis which are transcriptionally induced after ozone treatment, and thus they could sense ROS through redox modifications of their extracellular domain. Corresponding knock-out lines lead to sensitivity to extracellular ROS resulting in subtle lesion formation upon ozone treatment indicating their involvement in ROS signaling.…”
Section: Oxidative Burst Ros In Plant/microbe Interactionmentioning
confidence: 99%
“…Several mutants altered in hormone biosynthesis or signalling showed also changes in ozone-induced transcriptional responses. 134 Gauthier et al 135 have identified two members of the cysteine-rich receptor-like kinase gene family and a leucine-rich repeat (LRR-RLK) protein in Arabidopsis which are transcriptionally induced after ozone treatment, and thus they could sense ROS through redox modifications of their extracellular domain. Corresponding knock-out lines lead to sensitivity to extracellular ROS resulting in subtle lesion formation upon ozone treatment indicating their involvement in ROS signaling.…”
Section: Oxidative Burst Ros In Plant/microbe Interactionmentioning
confidence: 99%
“…8D). CRK expression has been shown to be modulated in response to ROS-and cellular redox state-related stresses (Lehti-Shiu et al, 2009;Wrzaczek et al, 2010;Bourdais et al, 2015). Moreover, CRKs are thought to be involved in cellular redox and apoplastic ROS sensing by the presence of conserved Cys residues in their apoplastic domain.…”
Section: The Apoplastic Redox State Influences Cellular Metabolismmentioning
confidence: 99%
“…Cysteine-rich Receptor Kinases (CRKs) belonging to DUF26 class proteins are known to mediate biotic and abiotic stress responses by activating ABA, SA, and JA hormone signaling [52,53]. Six transcripts related to Domain of Unknown Function 26 (DUF26) RLKs were also altered in a comparison between RB and SB after greenbug infestation (Fig.…”
Section: Perception and Early Signalingmentioning
confidence: 99%
“…4A). The receptor kinases including LRR and CRKs are shown to activate downstream signals by inducing production of ROS [52].…”
Section: Perception and Early Signalingmentioning
confidence: 99%